SDSS J075217.84 + 193542.2: X-ray weighing of a secondary BH - Titarchuk, Lev; Seifina, Elena (Frontiers in Astronomy and Space Sciences, 2024)
Precise measurements of black hole (BH) masses are necessary to understand the coevolution of these sources and their host galaxies. Sometimes in the center of a galaxy, there is not one but two BHs. The BH duality of the quasar nucleus SDSS J075217.84 + 193542.2 (herein referred to as SDSS J0752) was recently proposed based on the observed strict periodicity of optical emission from the source. We tested this assumption using X-ray observations obtained using Swift/XRT (2008–2010). We fitted the SDSS J075217 spectrum using a Comptonization model and discovered soft X-ray variability in the 0.3–10-keV energy range. We pursued a scenario in which two supermassive BHs at the center of SDSS J0752 form a pair, and the less massive (secondary) BH periodically crosses/punctures the disk around the more massive (primary) BH. We associated these periodic crossings with tidal disruptions of the disk and, as a consequence, with an increase in X-rays observed as a flare in SDSS J0752. During such an X-ray flare event (2008–2010), we discovered a change in the source spectral states and the photon index saturation at the Γ ∼ 3 level with mass accretion rate Ṁ. For BH mass scaling, we used OJ 287, M101 ULX–1, and HLX–1 ESO 243–49 as reference sources and found that MSDSS = 9 × 107 solar masses, assuming that dSDSS = 500 Mpc. Thus, we obtained a lower limit to a BH mass due to the unknown inclination. In addition, we used the virial mass of the secondary BH based on Hα-line measurements, and we estimated the inclination of the binary at SDSS J0752, i = 80°, using a scaling technique.